2013
DOI: 10.1111/jace.12568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Y2Si2O7/ZrO2 Composites and Their Composition – Mechanical Properties – Tribology Relationships

Abstract: In this work, novel Y2Si2O7/ZrO2 composites were developed for structural and coating applications by taking advantage of their unique properties, such as good damage tolerance, tunable mechanical properties, and superior wear resistance. The γ‐Y2Si2O7/ZrO2 composites showed improved mechanical properties compared to the γ‐Y2Si2O7 matrix material, that is, the Young's modulus was enhanced from 155 to 188 GPa (121%) and the flexural strength from 135 to 254 MPa (181%); when the amount of ZrO2 was increased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The adhesion of the Y 2 SiO 5 layer to both the TGO and the GZO topcoat was good, probably related to compatible CTE values. For yttrium monosilicate CTE values of (5–8) × 10 −6 K −1 were determined , quite matching those of GZO, chromia and MASC substrate given above. The yttrium silicate layer seems to reduce the localized degradation of the B‐containing M 7 Si 6 ‐based bond coat at the edges of the MASC coupons.…”
Section: Discussionsupporting
confidence: 68%
“…The adhesion of the Y 2 SiO 5 layer to both the TGO and the GZO topcoat was good, probably related to compatible CTE values. For yttrium monosilicate CTE values of (5–8) × 10 −6 K −1 were determined , quite matching those of GZO, chromia and MASC substrate given above. The yttrium silicate layer seems to reduce the localized degradation of the B‐containing M 7 Si 6 ‐based bond coat at the edges of the MASC coupons.…”
Section: Discussionsupporting
confidence: 68%
“…162 Thus, wear characteristics in different environments need to be well understood. Sun et al 163 To improve the mechanical and tribological properties of c-Y 2 Si 2 O 7 , Sun et al 164 developed a series of Y 2 Si 2 O 7 / ZrO 2 composites, which are promising as protective coatings against thermal loads and chemical attack. 165 Compared to c-Y 2 Si 2 O 7 , c-Y 2 Si 2 O 7 /ZrO 2 composites showed improved mechanical properties, e.g.…”
Section: Tribological Properties Of Y-si-o Oxidesmentioning
confidence: 99%
“…Experimental trials have proved that yttrium silicates are promising candidates for environmental/thermal barrier coatings (ETBC) due to their unique mechanical/thermal properties and superior environmental durability . Recent research also revealed that Y 2 Si 2 O 7 /ZrO 2 composite with improved mechanical properties and wear resistance is candidate for advanced ETBC against thermal load, chemical attack, and humid hot‐gas corrosion . In Sun's work, bulk γ‐Y 2 Si 2 O 7 and Y 2 SiO 5 samples have been processed via pressureless sintering and the thermal conductivity was obtained by measuring thermal diffusivity, heat capacity, and density.…”
Section: Introductionmentioning
confidence: 99%